KELAYAKAN INVESTASI PENGGANTIAN AKTIVA TETAP DENGAN ANGGARAN MODAL - Agam Sinaga (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
The goals of this study is to determine and analyze fixed asset replacement investment using capital budget analysis techniques. This is a quantitative descriptive research. The payback period for the old investment is 4 months, while the Profitability index (PI) for the new investment is 1 month. New investment is more feasible because the payback period is faster than the old investment. Net Present Value (NPV) of the old investment is IDR 654,551,514,096. New investments have a greater NPV value than old investments. New investment and old investment have a different rate of return. The rate of return on new investments is 4% while old investments only have a return rate of 1%. The Profitability Index (PI) of the old investment is 308 while the PI of the new investment is 203. Both investments generate profits for the company. PI. Old investment is better than new investment. However, this new investment is still considered feasible because the PI calculation requirement is that if the resulting value is greater than 1 then the investment is feasible.